2023
DOI: 10.3390/jcm12226983
|View full text |Cite
|
Sign up to set email alerts
|

18F-Fluorodeoxyglucose Positron Emission Tomography–Computed Tomography Findings of Polymyalgia Rheumatica in Patients with Giant Cell Arteritis

Elena Heras-Recuero,
Marta Martínez de Bourio-Allona,
Laura Cristina Landaeta-Kancev
et al.

Abstract: Objective: Giant cell arteritis (GCA) and polymyalgia rheumatica (PMR) are often overlapping conditions. We studied whether 18F-fluorodeoxyglucose (FDG) positron emission tomography–computed tomography (PET-CT) is useful in identifying PMR in the setting of large vessel (LV) GCA. Methods: LV-GCA patients diagnosed by PET-CT at a tertiary care center for a population of 450,000 people over a two-year period were reviewed. Scoring was performed based on potential significant FDG uptake at up to 16 sites in nine … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
0
0
Order By: Relevance
“…1.73±2.31; p<0.001). These results indicated that the number of affected extravascular sites was greater in patients with PMR [57]. Therefore, according with our data we feel that significant 18F-FDG-PET-CT uptake in the shoulder, greater trochanter, and lumbar interspinous areas can help identify PMR in patients with large vessel-GCA.…”
Section: What About Other Clinical Studies?supporting
confidence: 77%
See 2 more Smart Citations
“…1.73±2.31; p<0.001). These results indicated that the number of affected extravascular sites was greater in patients with PMR [57]. Therefore, according with our data we feel that significant 18F-FDG-PET-CT uptake in the shoulder, greater trochanter, and lumbar interspinous areas can help identify PMR in patients with large vessel-GCA.…”
Section: What About Other Clinical Studies?supporting
confidence: 77%
“…We assessed the effectiveness of 18F-FDG-PET-CT in identifying PMR in patients with large vessel-GCA [56]. To explore this and determine the best predictors for using 18F-FDG-PET-CT to clinically identify PMR in large vessel-GCA patients, we analyzed a cohort of 54 patients diagnosed with large vessel-GCA using 18F-FDG-PET-CT in our hospital [56,57]. We evaluated nine extravascular areas, encompassing 16 potential sites of involvement: the acromioclavicular and sternoclavicular joints (2 each), hips (2), shoulders (2), greater trochanters (2), ischial tuberosities (2), symphysis pubis entheses (2), and the cervical and lumbar interspinous processes.…”
Section: What About Other Clinical Studies?mentioning
confidence: 99%
See 1 more Smart Citation